The Role of Developmental Psychology in Supporting Arabic Language Learning for Early Childhood Education - Ulfah; Asep Maulana (CV. Creative Tugu Pena, 2026)
This study explore the connection between developmental psychology and children's Arabic language learning through literature due to the limited information available on optimal learning strategies for Arabic language learning in accordance with children's development. This study goals to analyze the process of cognitive, socio-emotional, and language development theories contributing to the development of Arabic language competency in children. A qualitative descriptive method was used, with a literature review of relevant research (stages of development and second language acquisition and Arabic). This findings indicate that children's cognitive ripeness, emotional readiness, and social interaction skills significantly influence their success in Arabic. Learning strategies aligned with the rule of developmental psychology also contribute significantly to children's language acquisition experiences, making learning more meaningful, effective, and enjoyable. Curriculum and learning environment aspects also portray a central actor in their Arabic language development. In conclusion, Arabic language teaching is highly affected by many reasons, such as strategies, environment, and curriculum applied in the classroom, with consideration of the procedure of children's psychological development for optimal learning outcomes.